Pendekatan Aksiologis Pendidikan Islam dalam Perspektif Islam dan Barat - M. Fazlurrahman H. (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2018)
The axiological approach in Islamic education is a discourse that is still very important and relevant for now. The whole process of Islamic education, both of which involve aspects of curriculum, learning, education personnel, student affairs, institutional management, and so on, has the same estuary or downstream, which supports axiological achievement in Islamic education. Then, it is also interesting to discuss, the interrelationships between the goals of Islamic and National education are already aligned or even overlapping. It is hoped that in the presentation this study can clearly convey the points on the objectives of Islamic education. So, it has an applicable educational axiology for Islamic education nationally. The method used by researchers is library research, which uses concepts that exist in the literature with research. The result, the philosophy of Islamic education in the country still has important foundations in presenting ideals as part of the theory of knowledge. In addition, there are still educational objectives that are difficult to achieve or not yet applicable. So it can be concluded that the authors of the philosophy of Islamic education have had academic awareness, the theory of purpose must be formulated before formulating the objectives of Islamic education from the perspective of philosophical studies. Unfortunately, that awareness cannot be realized by them, and cannot be used as a guide to formulate a systematic and comprehensive goal of Islamic education.